Pension reform in (F)BH with a special focus on gender issue (Public Sector Economics - submission site, 2021)
The purpose of the paper is to analyse and examine legal changes and requirements that affect retirement conditions and retirement rights for women in BH. After a discussion of the theoretical background of the gender gap in pensions internationally and in BH, an opinion survey related to pension system reforms was conducted in FBH. The results show that almost 50% of respondents disagree with the statement that women and men should retire at the same age. The results of the binomial logit regression conducted indicate that pensioners and those who are close to the retirement age are less likely, and men are more likely to respond positively to this statement. We conclude that there is a discrepancy between the desire to eliminate gender disparities in pensions and the willingness to conduct necessary reforms since they come as a bitter pill to swallow.